What Do (We Think) We Know about Indirectness in Literary Translation? A Tentative Review of the State-of-the-art and Possible Research Avenues - Pięta, Hanna (2017)
Studies with a specific focus on Indirect Translation (ITr) often suggest that little knowledge has been produced on this phenomenon, in spite of the frequent use of ITr in intercultural communication. Indeed, ITr is a phenomenon that combines a relatively small amount of research with vary ing terminology, lack of consensus on the conceptual level and limited methodological recommendations. Therefore, in an effort to address this gap, this paper seeks to foreground the concept of ITr, to put it (back?) on the map of Translation Studies and to encourage future empirical research. To do so, the paper will aim to (1) shed new light on the state-of-the art of current research on this phenomenon (by presenting the results of a brief bibliographical review); (2) add value to the current sum total of knowledge (by summarizing, exploring and challenging key assumptions typically made with regard to ITr); and (3) reflect on future research avenues (by indicating areas in need of urgent development). While doing so, the main focus will be on literary translation.